Systemic Functional Genre on Students’ Reading Literacy - Lidiyatul Izzah; Muhamad Sofian Hadi (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2018)
In the context of higher education, IT’s popularity and transparency has increased students’ higher awareness of writing in different evolving forms. It is undeniable that publishing scientific research is now seen more as success determinant in academic careers. Along with this demand, students need to deepen their advanced literacy and academic language skills to achieve good scientific writing. The aim of the study was to investigate the impact of Systemic Functional Genre approach in students’ reading literacy. A quantitative method of quasi-experimental design was carried out in this study. There were two groups involved: the experimental group (EG) and the control group (CG). During the implementation, both groups experienced in the different treatments. The population selected in this study was the second-semester learners of English Department, Muhammadiyah University of Jakarta. In selecting the sample, the researchers purposively choose two groups (n=60 students). To collect the data, the researchers implemented a reading test. Based on the research finding, the study indicated that the SFG-based Approach had a significant positive impact on improving the students’ reading literacy.